La preparación para la selección de la profesión del adolescente sordo. El papel de la familia. - Rodríguez Rodríguez, Beatriz (My University, 2016)
El artículo profundiza en las problemáticas actuales de la preparación de los escolares con discapacidad para la vida laboral, y el papel de la familia en la orientación profesional. Presenta una interpretación sobre el funcionamiento de los hogares con adolescentes sordos, enfatizando sus problemas educativos. Informa sobre una línea de investigaciones y experiencias realizadas con estos adolescentes y sus familias de la ciudad de Santa Clara, Cuba, para contribuir a una mejor selección de la profesión y la preparación para la vida laboral.

The article deepens into the challenges handicapped students can present in their future working life and the role of the families on their professional guidance. It reflects on the functioning of deaf children’s homes, emphasizing on their educational problems. Information is given about a series of researches and experiences carried out with these children and their families in Santa Clara city, Cuba,in order to contribute to a better selection of their future profession and to their preparation for future working life.
The preparation of deaf teenager for the selection of the profession. The role of the family.
Keywords: Orientación Profesional; Familia; Estudiantes con Discapacidad; Professional Orientation; Family; Handicapped Students